The Amino Acids Sensing and Utilization in Response to Dietary Aromatic Amino Acid Supplementation in LPS-Induced Inflammation Piglet Model - Duanmu, Qing; Tan, Bie; Wang, Jing; Huang, Bo; Li, Jianjun; Kang, Meng; Huang, Ke; Deng, Qiuchun; Yin, Yulong (Frontiers in Nutrition, 2022)
Dietary supplementation with aromatic amino acids (AAAs) has been demonstrated to alleviate intestinal inflammation induced by lipopolysaccharide (LPS) in the piglets. But the mechanism of AAA sensing and utilization under inflammatory conditions is not well-understood. The study was conducted with 32 weanling piglets using a 2 × 2 factorial arrangement (diet and LPS challenge) in a randomized complete block design. Piglets were fed as basal diet or the basal diet supplemented with 0.16% tryptophan (Trp), 0.41% phenylalanine (Phe), and 0.22% tyrosine (Tyr) for 21 days. The results showed that LPS treatment significantly reduced the concentrations of cholecystokinin (CCK) and total protein but increased leptin concentration, the activities of alanine transaminase, and aspartate aminotransferase in serum. Dietary supplementation with AAAs significantly increased the serum concentrations of CCK, peptide YY (PYY), and total protein but decreased the blood urea nitrogen. LPS challenge reduced the ileal threonine (Thr) digestibility, as well as serum isoleucine (Ile) and Trp concentrations, but increased the serum concentrations of Phe, Thr, histidine (His), alanine (Ala), cysteine (Cys), and serine (Ser) (P < 0.05). The serum-free amino acid concentrations of His, lysine (Lys), arginine (Arg), Trp, Tyr, Cys, and the digestibilities of His, Lys, Arg, and Cys were significantly increased by feeding AAA diets (P < 0.05). Dietary AAA supplementation significantly increased the serum concentrations of Trp in LPS-challenged piglets (P < 0.05). In the jejunal mucosa, LPS increased the contents of Ala and Cys, and the mRNA expressions of solute carrier (SLC) transporters (i.e., SLC7A11, SLC16A10, SLC38A2, and SLC3A2), but decreased Lys and glutamine (Gln) contents, and SLC1A1 mRNA expression (P < 0.05). In the ileal mucosa, LPS challenge induced increasing in SLC7A11 and SLC38A2 and decreasing in SLC38A9 and SLC36A1 mRNA expressions, AAAs supplementation significantly decreased mucosal amino acid (AA) concentrations of methionine (Met), Arg, Ala, and Tyr, etc. (P < 0.05). And the interaction between AAAs supplementation and LPS challenge significantly altered the expressions of SLC36A1 and SLC38A9 mRNA (P < 0.05). Together, these findings indicated that AAAs supplementation promoted the AAs absorption and utilization in the small intestine of piglets and increased the mRNA expressions of SLC transports to meet the high demands for specific AAs in response to inflammation and immune response.